Evidence-Based Surveillance Imaging Schedule After Liver Transplantation for Hepatocellular Carcinoma Recurrence. Issue 1 (January 2017) - Liu, Dan; Chan, Albert C. Y.; Fong, Daniel Y. T.; Lo, Chung-Mau; Khong, Pek-Lan
Abstract : Background: There is presently no evidence-based recommendation for surveillance of recurrent hepatocellular carcinoma after liver transplantation (LT). We aim to evaluate and develop evidence-based alternate surveillance imaging schedules for post-LT hepatocellular carcinoma patients. Methods: Imaging and pathologic reports for consecutive post-LT patients followed up by regular surveillance imaging from a single institution's prospective database were evaluated with institutional review board approval. Outcome variable was time to diagnosis of first recurrence post-LT by surveillance imaging. Recurrence-free survival times from alternative surveillance schedules were compared with the existing schedule (every 3 months) using a parametric frailty model. Expected delay (EpD) in diagnosis compared to the existing schedule was also computed for the alternate surveillance schedules. A P value less than 0.05 was considered to indicate a significant difference. Results: One hundred twenty-five patients (108 men; 59.4 ± 16.6 years) underwent 1953 computed tomography and 255 magnetic resonance imaging scans. Recurrence-free survival time was not significantly different in the first 5 years after LT when the imaging interval was extended from current every 3 months to every 6 months ( P = 0.786, EpD = 55 days). This alternative schedule incurred 10 (50.0%) fewer surveillance scans than the 20 in the original schedule, and a corresponding reduction in radiation dose (if involved) and cost during the 5-year follow-up period. Conclusions: In conclusion, modeled alternative surveillance schedules have the potential to reduce the frequency of scans without compromising surveillance benefits. Abstract : There is no evidence-based guideline to support the optimal frequency of surveillance of recurrent hepatocellular carcinoma after liver transplantation. The authors propose modeled alternative surveillance schedules that have the potential to reduce the frequency of imaging without compromising surveillance benefits.